Development Of ICT- Based Early Childhood Concept Teaching Book To Increase Pedagogic Competence For College Students Of PGPAUD - Sumarni, S.; Andika, W. D.; Utami, F.; Rantina, M.; Sazaki, Y.; Astika, R. T.; Rahardja, B.; Kurnia, N.; Priyanti, N.; Wondal, Rosita (Opción, 2019)
Pedagogic competence should be mastered by candidate for early childhood education teachers/ PAUD, one way by mastering the basic concepts of early childhood education. In fact, based on the needs analysis of the 79 college students of PAUD showed that students need the teaching books of the fundamental concept of ICT-based PAUD with free access, in Indonesian language , discussion per matter, equipped with text and images, references updates, written by authors who are competent in their fields so it is easy to be used by students. Such gap should be immediately resolved, so the research aims to develop teaching book of ICT-based on the basic concepts of PAUD in enhanc- ing the pedagogic competence of college students. The method that Research and Development uses with Dick and Carey design. This research sample is the student of PGPAUD UNSRI as many as 74 students. Implementation step in small group of 23 students, and a large group of 51 students. Based on the data analysis test results, the ICT-based KDPAUD teaching book application that have been developed proved to be valid, practical and effective. The results proved that the application of the ICT-based KD PAUD teaching book that have been developed can increase the pedagogic competence of PGPAUD UNSRI students, so that candidate teachers are able to maximize learning to optimize children’s growth in early age.